PENGARUH PENGAWASAN TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS PEKERJAAN UMUM KABUPATEN KUTAI TIMUR - Setiawan, Riki (PREDIKSI, 2016)
This research aims to find out whether there is a positive influence between Supervision with the employees performance by the study on Dinas Pekerjaan Umum Kabupaten Kutai TimurThe population in this research is all employees the amount as much as 20 people, considering the number of taken relatively in small scale so this research using the census method, namely the population made as respondents.Based on the explanation above, analysis tool used in this research is Koefesien Correlation Product moment. From the result of the calculation shows that there is a significant impact between the monitoring of the performance of employees inÂ Dinas Pekerjaan Umum Kabupaten Kutai Timur. This is based on the results of the calculation that rhitung greater than rtabel namely 0,982 > 0,561 for critical value on n = 20 with tariff of the significance = 0.01. For n = 20 then both variables have the level of the very strong relations.After r count acquired, then the author held a hypothesis testing using t test from the results of the test of this hypothesis, thitung value of 22,058 meanwhile to the prices of keritis from 2,552 ttabel value is that means interfere decreasing that ttest > ttabel namely 22,058 > 2,552 with critical value n - 20 with equal significance 0.01. It can be said that there is a very strong influence from the variables surveillance of employees performance variable in Dinas Pekerjaan Umum Kabupaten Kutai Timur